Modernization of Social Security System Legal Regulation in Kazakhstan: Experience and Standards of the OECD Members Implementation - MUKHAMADIYEVA, Gulzhan N.; MUKALDYEVA, Gulyiya; KARASHEVA, Zhanar T.; KHAMZIN, Amangeldy Sh.; BURIBAYEV, Yermek A.; KHAMZINA, Zhanna A. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).21, 2018)
The main idea of the study is to substantiate legislative proposals, recommendations on the introduction in Kazakhstan of the standards of social protection systems of OECD member countries. As a result of the research, conclusions were drawn up aimed at improving the norms of the current legislation and law enforcement practice, and on modernizing measures to implement social policy in the context of the process of the progressive development of Kazakhstan as a social state. The purpose of the article is to develop recommendations, proposals focused on the further development of the legal framework of the social sphere in Kazakhstan as a perspective orientation of legal science and as the most important mechanism for implementing a number of constitutional human and citizen rights. The purpose of the study is limited to four main areas, namely the analysis of social protection systems of OECD countries in the event of the following social risks: disability, poverty, retirement age, and social security guarantees for the family and the child. The applied objective of the work is related to the justification and elaboration of a set of proposals to improve the current social legislation, proposals to increase the effectiveness of state social policy, to introduce the standards of OECD countries in the field of social protection into Kazakhstan's domestic law. Targeted users of the research results are the interested state bodies, the scientific community, students, undergraduates, doctoral students, a wide range of persons interested in the problems of legal provision of state social policy, social human rights.